SOSIALISASI PEMILU PILKADA 2024 DI DESA TANJUNG JAYA KAMPAR - Rahma, Sitti; Museliza, Virna; Al-Kadafi, Muammar; Mashuri, Mashuri; Rusdi, Rusdi; Afrizal, John; Nurdiana, Nurdiana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
General elections are one form of political participation as a manifestation of the sovereignty of the people, where in general elections, the people are given the freedom to choose a candidate for leader who is worthy of occupying the position based on the mandate given. The people are still faced with money politics to influence the election process for someone, the level of awareness and participation of the people who think their votes are not important in the regional head elections which will take place on November 27, 2024. One way that can be taken to increase participation, understanding, and political awareness of a person is through political education, which aims to foster political awareness of the people who have the right to vote and are registered in their respective regions, a method of service by creating a problem-solving framework, strategic intermediate target groups, and steps for service activities. Service activities were carried out in Tanjung Jaya Village, Koto Kampar Kiri Hulu District, Kampar Regency. The results of the community service activities can be concluded that fathers and mothers and the younger generation who are over 17 years old or who are married know and understand the importance of participating in regional head elections with the process and procedures for holding elections, the rights and obligations of voters, money politics and political funds, money politics in Islam and becoming smart voters so that they are wiser based on their conscience without money politics.